Assessment of Spatial and Temporal Trend of Groundwater Salinity in Jaffna Peninsula and Its Link to Paddy Land Abandonment - Tharani, G.; Kumar, L.; Mikunthan, T. (MDPI, 2020)
Salinization is an explicit global threat faced by coastal low lands. The increased seawater ingression into groundwater due to various climatic and anthropogenic factors affects functioning of ecosystems, biodiversity and the sustainability of coastal agriculture. This study was undertaken to investigate the changes in groundwater salinity in Jaffna Peninsula over a 20-year period and its relationship with paddy land abandonment. Permanently abandoned paddy areas were mapped using historical Landsat images, while groundwater salinity changes in 63 agricultural wells for the period 1999 to 2019 were analysed. The trend in salinity, including proximity to the coast, was examined. The results showed that approximately 8178 ha (43% of total paddy land) of paddy lands had been permanently abandoned while the groundwater salinity had increased by 1.6-fold over the last two decades. An increasing salinity trend with decreasing distance from the coast was observed. Presently, nearly 59% of the wells showed salinity levels that were unsuitable for crop irrigation. The results underline the need for urgent and effective management of groundwater resources in order to maintain the sustainability of the existing paddy lands and ensure availability of potable water for consumption along the coastal low land areas of Jaffna Peninsula.
Keywords: Groundwater; Salinity; Coastal salinity; Sustainability; Jaffna; Coastal agriculture